Akar Radikalisme di Ruang Kelas: Eksplorasi Faktor Pemicu di Lembaga Pendidikan Islam - Zainuddin; Erik Pebrikarlepi; Ulfa Hoyriah; Siti Murtosiah (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
Radicalism poses a significant threat to social cohesion and national unity in Indonesia. This research explores the strategic role of education in preventing the spread of radical ideologies and building a tolerant society. The primary focus is analyzing the systemic design of education to promote contextual and inclusive religious values. Employing a qualitative-descriptive approach, the study investigates how curriculum, pedagogy, and teacher roles can shape religious narratives supporting peace and humanity. The research reveals that rigid and doctrinal religious education potentially triggers radicalization, while dialogical and contextual approaches can effectively counter the spread of extremist ideologies. Key findings underscore the need for transforming religious education by emphasizing deep understanding of tolerance, conflict resolution, and diversity. The primary contribution of the research is a model of educational approach integrating progressive religious interpretations with universal humanitarian values. The study's implications include educational policy recommendations that can strengthen social capital and prevent radicalization among Indonesian youth.